Serum exosomal hsa-circ-0004771 modulates the resistance of colorectal cancer to 5-fluorouracil via regulating miR-653/ZEB2 signaling pathway - Qiao, Xiao-Xue; Shi, Hui-Bo; Xiao, Li (Cancer cell international, 2023)
BackgroundDrug resistance is a major obstacle causing chemotherapy failure, and enabling cancer progression. Exosome excreted by cancer cells is participated in cancer progression and chemoresistance, and can be used as an prognostic biomarker. Previous studies have revealed that serum exosomal hsa-circ-0004771 is over-expressed in colorectal cancer (CRC) sufferers and suggested it as a predictive biomarker for early diagnosis and prognosis of CRC. This work will to investigate the role and mechanism of serum exosomal hsa-circ-0004771 in mediating resistance to 5-fluorouracil (5-FU) in CRC.MethodsSerum and tissue samples were collected from 60 patients with CRC/ benign intestinal disease, and 60 healthy control. Exosomes were isolated and identified from serum samples and cell cultured media with TEM, WB, NTA, and flow cytometry. qRT-PCR and WB were performed to evaluate mRNA expressions of exosomal has-circ-0004771 and miR-653, and ZEB2 protein expression, respectively. Cell proliferation, migration, invasion, and apoptosis abilities were assessed with BrdU and colony formation assay, wound-healing assay, and flow cytometry, respectively.ResultsExosomal hsa-circ-0004771 was over-expressed in CRC serum and cell cultured media, while miR-653 was lower-expressed in CRC tissues and cells. Negative correlations existed between exosomal hsa-circ-0004771 in the patients’ serum/cell culture media and miR-653 in CRC tissues/cells, and between miR-653 and ZEB2 in CRC cells. Exosomal hsa-circ-0004771 in CRC cell cultured media was positively related to ZEB2 in CRC cells. MiR-653 was associated with poor prognosis of CRC patients, and its upregulation restrained CRC cell proliferation, migration and invasion, and stimulated apoptosis. Exosomal hsa-circ-0004771 was higher-expressed in 5-FU-resistant CRC serum and cell cultured media, miR-653 was downregulated and ZEB2 was overexpressed in 5-FU-resistant CRC cells. In vitro, exosomal hsa-circ-0004771 in cell cultured media may be involved in 5-FU-resistance by modulating miR-653/ZEB2 pathway.ConclusionsmiR-653 plays as a tumour suppressor in CRC progression, and serum exosomal hsa-circ-0004771 may be a predictive biomarker for 5-FU-resistance in CRC patients, potentially through miR-653/ZEB2 axis.